Literarno branje in razvijanje literarne zmožnosti pri književnem pouku slovenščine v digitalni dobi - Žbogar, Alenka (Slavia Centralis, 2025)
This article, examines how reading fiction within learning literature in Slovene language classes in the digital age is realized as a dialogic process, organized in stages, that contributes to the holistic development of literary competence. Parallels between literacy and literary competence and reading (fiction) are explored in terms of their effects, the medium (print vs. on-screen texts), and pupils’ developmental characteristics. Results from the interna tional literacy studies PIRLS and PISA are examined, finding that literary competence is not measured in the latter. Influences of the digital environment on attention, reading motivation, and reading strategies are delved into, leading to the conclusion that the digital age requires a reconsideration of didactics of Slovene language and literature.
Keywords: bralna pismenost; developmental characteristics of pupils; digital age; digitalna doba; effects of reading fiction; književnost pri pouku slovenščine; literacy; literarna zmožnost; literarno branje; literary competence; literature in Slovene language classes; on-screen texts; print texts; razvojne posebnosti učencev; reading fiction; tiskana besedila; učinki literarnega branja; zaslonska besedila